2013
DOI: 10.1089/ars.2012.4568
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species and Antioxidants in Pulmonary Hypertension

Abstract: Significance: Pulmonary hypertension is a devastating disorder without any available treatment strategies that satisfactorily promote the survival of patients. The identification of new therapeutic strategies to treat patients with pulmonary hypertension is warranted. Recent Advances: Human studies have provided evidence that there is increased oxidative stress (lipid peroxidation, protein oxidation, DNA oxidation, and the depletion of smallmolecule antioxidants) in patients with pulmonary hypertension. A vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
96
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(107 citation statements)
references
References 53 publications
2
96
1
1
Order By: Relevance
“…10 Finally, recent reports have linked disruption in the scavenging of reactive oxygen species to the progression and pathology of PH. 11,12 As an antioxidant, vitamin C may have multiple beneficial effects in scavenging reactive oxygen species and preventing downstream pulmonary vasoconstriction.…”
Section: Figurementioning
confidence: 99%
“…10 Finally, recent reports have linked disruption in the scavenging of reactive oxygen species to the progression and pathology of PH. 11,12 As an antioxidant, vitamin C may have multiple beneficial effects in scavenging reactive oxygen species and preventing downstream pulmonary vasoconstriction.…”
Section: Figurementioning
confidence: 99%
“…An increased production of reactive oxygen species (ROS) may result from activated nicotinamide adenine dinucleotide phosphate reduced oxidases and dysfunctional mitochondria (48,49). ROS can oxidize tetrahydrobiopterin, an essential cofactor of eNOS, to dihydrobiopterin, which leads to eNOS uncoupling, a process by which eNOS produces superoxide instead of NO.…”
Section: Edno As a Paracrine Regulatormentioning
confidence: 99%
“…[7][8][9] Accumulating data have shown that oxidative stress plays important roles in mediating pathological changes in the pulmonary arterioles and the right ventricle. [10][11][12] …”
Section: Reactive Oxygen Species (Ros)mentioning
confidence: 99%